Distribution of Subsidized Fuel for Fishermen in The Utilization of Maritime Potential in Bintan Regency - Elyza Riani; Yossi Oktalina (Journal of Maritime Policy Science, 2025)
Bintan Regency, an area with abundant maritime resources, heavily depends on the fisheries sector for its economic development, with a significant portion of the population working as fishermen. However, the full utilization of maritime potential in this region remains suboptimal, primarily due to limited access to subsidized fuel, a vital resource for fishing operations. Fuel subsidies have long been a financial and logistical challenge in Indonesia, exacerbated by declining domestic oil production and increasing reliance on imports. This study aims to investigate the impact of fuel subsidy distribution on fishermen’s livelihoods and the broader maritime economy in Bintan Regency. Using a qualitative research approach, data were collected through structured interviews with fishermen, local authorities, and maritime experts, as well as through analysis of secondary data from policy documents and academic sources. The findings indicate that while fuel subsidies are intended to alleviate the economic burden on fishermen, implementation inconsistencies, inadequate infrastructure, and bureaucratic hurdles have hindered their effectiveness. Many fishermen still rely on traditional tools and face high operational costs due to limited access to subsidized diesel, resulting in reduced income and economic insecurity. To address these issues, the Bintan Regency government has proposed increasing the quota of subsidized fuel and introducing digital systems such as fuel cards to improve distribution transparency.